2018
DOI: 10.1177/1179551418785135
|View full text |Cite
|
Sign up to set email alerts
|

Should Symptoms Be Considered an Indication for Parathyroidectomy in Primary Hyperparathyroidism?

Abstract: Asymptomatic primary hyperparathyroidism is a very common endocrine condition, yet management of this disease process remains controversial. Primary hyperparathyroidism can lead to a myriad of symptoms which not only decreases the quality of life of patients but also increases the risk of cardiovascular disease, osteoporosis, and kidney stones. Parathyroidectomy is the only known cure for the disease. This review explores the definition of asymptomatic primary hyperparathyroidism, the burden of disease, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…PTH acts as on G-protein-coupled receptors to activate phospholipase V on myocytes and protein kinase A on vascular endothelium [8]. The proposed mechanisms of development of cardiovascular dysfunction in PHPT include: 1) Development of hypertension: driven by alteration in vasodilatory properties of endothelium and/or hyperaldosteronism as a result of activation of renin-aldosterone-angiotensin axis (RAAS); 2) Development of LVH: driven by PTH mediated hypertrophy of cardiac myocytes, endothelial dysfunction [19]; 3) Calcification of myocardium and aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTH acts as on G-protein-coupled receptors to activate phospholipase V on myocytes and protein kinase A on vascular endothelium [8]. The proposed mechanisms of development of cardiovascular dysfunction in PHPT include: 1) Development of hypertension: driven by alteration in vasodilatory properties of endothelium and/or hyperaldosteronism as a result of activation of renin-aldosterone-angiotensin axis (RAAS); 2) Development of LVH: driven by PTH mediated hypertrophy of cardiac myocytes, endothelial dysfunction [19]; 3) Calcification of myocardium and aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, angiotensin II may have an acute and direct effect on PTH synthesis and secretion [20]. In addition, PTH may play a direct effect on the RAAS system, through potentiation of angiotensin II induced aldosterone secretion from the zona glomerulosa cells [19][20][21][22]. It has been suggested that aldosterone may stimulate secretion of PTH by one of two mechanisms: either by virtue of a secondary hyperparathyroidism induced by a chronic aldosterone excess inducing hypercalciuria and hypocalcaemia [23], or by a more direct effect mediated via mineralocorticoid receptors in the parathyroid tissue [24].…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the patients undergoing asymptomatic primary hyperparathyroidism were selected based on the following criteria: serum calcium levels 1 mg/dl above the upper limit of the normal range (>11.5 mg/dl), below 50 years old, glomerular filtration rate (eGFR) < 60 mL/min, a history of fracture fragility, and T-score <2.5 SD. 16 The exclusion criteria were as follows: being unwilling to continue the study, experiencing unsuccessful PTX, using Estrogen and Progestin, and taking vitamin D supplements. 17 Factors such as serum phosphate, 1,25(OH) 2 D 3 , calcium vitamin D, alkaline phosphatase (ALP), PTH, urea, creatinine (Cr), FGF23, and 24-hour urine for calcium were first checked in the same laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…However, this is disputed as some claim that a truly asymptomatic PHPT patient is quite rare. 4 Whereas most asymptomatic patients do not exhibit disease progression, as defined by worsening hypercalcemia, hypercalciuria, bone disease, and/or nephrolithiasis, 5 some individuals do progress and would benefit from surgery. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…However, this is disputed as some claim that a truly asymptomatic PHPT patient is quite rare. 4 Whereas most asymptomatic patients do not exhibit disease progression, as defined by worsening hypercalcemia,…”
mentioning
confidence: 99%